Sex, size and habitat complexity effects on emergence latency and latency to locate food of the invasive porthole livebearer (Poeciliopsis gracilis). - Esteban Aceves-Fonseca; Abigail Santiago-Arellano; Morelia Camacho-Cervantes (PLoS ONE, 2022)
Biological invasions are considered the second major cause of plant, amphibian, reptile, and mammal loss worldwide. Like islands, freshwater ecosystems are especially susceptible to the negative impacts of invasions. The porthole livebearer (Poeciliopsis gracilis), recently identified as invasive in the Mexican Central Plateau, is increasing its populations and could impact freshwater ecosystems like its cousin species the guppy (Poecilia reticulata). Risk-taking behaviours, such as emergence latency, are recognised as key characteristics to invasion success and Poeciliid females can establish a viable population by themselves (due to their multiple paternity broods). We investigated the emergence latency and latency to locate food in simple and complex environments of porthole livebearers, including the effect of their size and sex. For both sexes, bigger fish emerge less times and take longer to do so, but females are faster to exit the refuge than males. We found no differences in porthole livebearer's behaviour in complex or simple habitats, and no significant differences between sex, size or treatment in the time to locate food after exiting the refuge. Our results suggest that the benefit of faster emergence from the refuge in porthole livebearers in novel environments could be higher for females. We consider that porthole livebearer females being bolder could contribute to the invasion success of the species. Our study points at females and smaller fish as being the more likely to explore novel environments, which could contribute to understanding how the invasions by the porthole livebearer are driven.